2005
DOI: 10.1167/iovs.04-1235
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Mitochondrial Apoptotic Pathway in a Rat Model of Central Retinal Artery Occlusion

Abstract: This model is highly relevant to clinical manifestations of CRAO and is an ideal animal model for research. These findings indicate the activation of the mitochondrial pathway in ischemic retina induced by CRAO. The model provides a better understanding of ischemia-induced retinal apoptosis. Antiapoptosis therapy directly targeting the mitochondrial pathway in CRAO or other retinal ischemic diseases may be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 40 publications
1
35
2
Order By: Relevance
“…A previous study on animals showed that the correlation of the ERGs and histological changes with the residual retinal circulation variables was not significant [8]. However, in good agreement with the report by Machida et al [11], who found that the PhNR was the most affected wave following a CRAO, our results showed that the PhNR was significantly reduced in eyes with CRAO.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A previous study on animals showed that the correlation of the ERGs and histological changes with the residual retinal circulation variables was not significant [8]. However, in good agreement with the report by Machida et al [11], who found that the PhNR was the most affected wave following a CRAO, our results showed that the PhNR was significantly reduced in eyes with CRAO.…”
Section: Discussionsupporting
confidence: 91%
“…The RGCs are more vulnerable to ischemia and suffer irreversible damage soon after an occlusion, which is supported by histopathologic findings showing apoptotic changes in this layer [8]. The photopic negative response (PhNR) of the photopic ERG which originates from the neural activity of the RGCs has been used to assess the function of RGCs in experimental animals [9, 10] and in humans with retinal and optic nerve pathology [10,11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 78%
“…One study revealed that cells in the inner retina especially RGCs are more vulnerable to ischemic damage compared to cells of the outer retina (19). Apoptosis, as detected by TUNEL staining, has been observed in the GCL, INL, and outer nuclear layer of the retina (20). Apoptosis of the ganglion cells is progressive and irreversible (20); therefore, anti-apoptosis therapy in retinal ischemic diseases may be beneficial to improve retinal functions.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis, as detected by TUNEL staining, has been observed in the GCL, INL, and outer nuclear layer of the retina (20). Apoptosis of the ganglion cells is progressive and irreversible (20); therefore, anti-apoptosis therapy in retinal ischemic diseases may be beneficial to improve retinal functions. ReIran Red Crescent Med J.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Other common mechanisms include altered aquaporin expression, 12,13 oxidative stress, 14,15 and increases in proapoptotic and decreases in antiapoptotic markers. 16,17 Increased inflammation occurs in both conditions, including increased activation of glial cells and macrophages, 18,19 increased levels of inflammatory cytokines (IL-6, TNF-a, and so on), 20,21 and nuclear factor kappa-light-chain-enhancer of active B cells (NF-jB) pathway activation. 22,23 The high degree of mechanistic overlap, as well as the presence of central nervous system tissue in both cerebral and retinal/optic nerve ischemia, could allow for treatment crossover between diseases.…”
mentioning
confidence: 99%